Determinants of quality of life among elderly patients with type 2 diabetes in northwest of iran: based on problem areas in diabetes - Moghaddam, Hamed Rezakhani; Sobhi, Eslam; Soola, Aghil Habibi (Frontiers in Endocrinology, 2022)
Background Diabetes is a metabolic disease characterized by chronic hyperglycemia, leading to damage to various organs of the patients and a reduction of their life expectancy and quality of life (QOL). The aim of this study was to explore the determinants of the QOL based on the Problem Areas in Diabetes (PAID). Methods This cross-sectional study was carried out in an Iranian diabetic clinic in Ardabil. The PAID, the short form health survey (SF-12), and the sociodemographic questionnaire were all employed. Using the census sample method, 266 elderly people with type 2 diabetes from the lone diabetic clinic at Ardabil took part in this study. One-way ANOVA, t-test, one-sample Kolmogorov–Smirnov test, and multiple regression were used to analyze the data. Results Data analysis showed that there was a statistically negative significant relationship between the QOL dimensions and the triple domains of PAID (p < 0.01). In the final model of the predictors of the QOL, treatment barriers, psychological distress related to diabetes management, the type of treatment, age, and the duration of diabetes were statistically significant predictors of the QOL dimensions (p>0.05). Conclusion Individual characteristics and factors connected to health services should be prioritized in any intervention program aimed at improving the QOL of elderly patients with diabetes. Psychological distress should be considered in addition to regular physician visits.